Novel RSPH4A Variants Associated With Primary Ciliary Dyskinesia–Related Infertility in Three Chinese Families - Wang, Lin; Wang, Rongchun; Yang, Danhui; Lu, Chenyang; Xu, Yingjie; Liu, Ying; Guo, Ting; Lei, Cheng; Luo, Hong (Frontiers in Genetics, 2022)
Background: The radial spoke head component 4A (RSPH4A) is involved in the assembly of radial spokes, which is essential for motile cilia function. Asthenoteratozoospermia in primary ciliary dyskinesia (PCD) related to RSPH4A variants has not been reported. Materials and Methods:RSPH4A variants were identified and validated using whole-exome and Sanger sequencing in three unrelated Chinese families. High-speed video microscopy analysis (HSVA) was performed to measure the beating frequency and pattern of nasal cilia of the patients and healthy control. Papanicolaou staining and computer-aided sperm analysis were performed to analyze the morphology and motility of the sperm in patient 1. Immunofluorescence was adopted to confirm the structure deficiency of sperm and nasal cilia. Results: Patient 1 from family 1 is a 22-year-old unmarried male presented with bronchiectasis. Semen analysis and sperm Papanicolaou staining confirmed asthenoteratozoospermia. Novel compound heterozygous RSPH4A variants c.2T>C, p.(Met1Thr) and c.1774_1775del, p.(Leu592Aspfs*5) were detected in this patient. Patients 2 and 3 are from two unrelated consanguineous families; they are both females and exhibited bronchiectasis and infertility. Two homozygous RSPH4A variants c.2T>C, p.(Met1Thr) and c.351dupT, p.(Pro118Serfs*2) were detected, respectively. HSVA showed that most of the cilia in patients 1 and 3 were with abnormal rotational movement. The absence of RSPH4A and RSPH1 in patient 1’s sperm and patient 3’s respiratory cilia was indicated by immunofluorescence. Patient 2 died of pulmonary infection and respiratory failure at the age of 35 during follow-up. Conclusion: Dysfunctional sperm flagellum and motile cilia in the respiratory tract and the fallopian tube were found in patients with RSPH4A variants. Our study enriches the genetic spectrum and clinical phenotypes of RSPH4A variants in PCD, and c.2T>C, p.(Met1Thr) detected in our patients may be a hotspot RSPH4A variant in Chinese.